2015
DOI: 10.5539/mas.v9n6p87
|View full text |Cite
|
Sign up to set email alerts
|

Organophosphate Residue in Different Land Use in Mojogedang Karanganyar Central Java Indonesia

Abstract: The use of inorganic pesticides result in residues of pesticides in the environment. Mojogedang is an area that has implemented a system of organic farming but also there are farmers who apply chemical pesticides. Pesticides are commonly used by farmers in Mojogedang causing residues, such as organophosphate. Organophosphates contains the active ingredient with a relatively long persistence in the environment and dangerous that it needs a study to investigate the organophosphate residues. The aims of this rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 21 publications
0
4
1
Order By: Relevance
“…The mean concentrations of profenofos recorded at all sites were below the US MRL of 0.05 mg/kg for agricultural soils. In a similar study Supriyadi et al (2015), reported profenefos concentrations that were relatively higher than the mean values reported in this work. This could be due to the extent of pollution of soils with profenefos containing pesticides in that study area.…”
Section: Organophosphorus Pesticide Residues In Soil Samplescontrasting
confidence: 56%
“…The mean concentrations of profenofos recorded at all sites were below the US MRL of 0.05 mg/kg for agricultural soils. In a similar study Supriyadi et al (2015), reported profenefos concentrations that were relatively higher than the mean values reported in this work. This could be due to the extent of pollution of soils with profenefos containing pesticides in that study area.…”
Section: Organophosphorus Pesticide Residues In Soil Samplescontrasting
confidence: 56%
“…PH H 2 O in horticultural soil sample is 5.7 and sandy clay type of soil. In this study, the soil pH of the ten test samples ranged from 6.4 to 8.1 [7].…”
Section: Resultsmentioning
confidence: 89%
“…Our findings also indicate a prevalent resistance among vector to organophosphates in barren land. These areas are often characterized by irrigation practices to facilitate agriculture, as noted in [ 27 ]. The agriculture activities in such drylands are susceptible to severe pest infestations, resulting in high use of inorganic pesticides, including organophosphates, to combat these pests [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…These areas are often characterized by irrigation practices to facilitate agriculture, as noted in [ 27 ]. The agriculture activities in such drylands are susceptible to severe pest infestations, resulting in high use of inorganic pesticides, including organophosphates, to combat these pests [ 27 ]. Additionally, the use of organophosphates extends beyond agriculture for the control of a wide range of public health pests across different land use and land cover (LULC) classes [ 28 ], Confirmed resistance of malaria vectors to organophosphates in irrigated regions has also been documented [ 29 ], suggesting that the extensive application of these chemicals is a likely catalyst for the development of resistance in both targeted and non-targeted insect populations, including vectors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation